Synthesis and cherization of low-dimensional materials - Alessandro, Francesca; Critelli, Salvatore; Caputi, Lorenzo; Cupolillo, Anna (Università della Calabria, 2020)
The main aim of this thesis is to synthesize and study low-dimensional materials, with special focus on: silicene, PtTe2, carbon nano-onions and activated carbon. The first section of this work describes the study of the collective modes in silicene and PtTe2. Silicene, the silicon equivalent of graphene, is attracting increasing scientific and technological interest in view of the exploitation of its exotic electronic properties. This material has been theoretically predicted to exist as a free-standing layer in a low-buckled, stable form, and can be synthesized by the deposition of Si on appropriate crystalline substrates. Using a combined experimental (High-Resolution Electron-Energy-Loss Spectroscopy, HR-EELS) and theoretical (Time Dependent Density Functional Theory, TDDFT) approach the electronic excitations of two phases of silicene growth on silver were studied showing that silicene grown in a mixed phase on Ag(111), preserves part of the semimetallic character of its freestanding form, exhibiting an interband π-like plasmon. Recently, the PtTe2 has emerged as one of the most promising among layered materials ―beyond graphene‖. In this work, the electronic excitations of the bulk PtTe2 were investigated by means of EELS and DFT detecting a sequence of modes at 3.9, 7.5 and 19.0 eV. The comparison of the excitation spectrum with the calculated density of states (DOS) allowed to ascribe spectral features to transitions between specific electronic states. Moreover, it has been observed that, in contrast to graphene, the high-energy plasmon in PtTe2 gets red-shifted by 2.5 eV with increasing thickness. The second section of this thesis reports the synthesis of polyhedral carbon nano-onions by arc discharge in water and the electrochemical performance of activated carbon in aqueous electrolytes. CNOs, in their spherical or polyhedral forms, represent an important class of nanomaterials, due to their peculiar physical and chemical properties. In this work, polyhedral carbon nano-onions (CNOs) were obtained by underwater arc discharge of graphite electrodes using an innovative experimental arrangement. Dispersed nanomaterials and a black hard cathodic deposit were generated during the discharges and studied by scanning electron microscopy (SEM), transmission electron microscopy (TEM), Raman spectroscopy and thermogravimetric analysis (TGA). A model for the formation of the deposit was proposed, in which the crystallization is driven by an intense temperature gradient in the space very close to the cathode surface. Electric double layer capacitors (EDLC) are gaining increasing popularity in high power energy storage applications. Novel carbon materials with high surface area, high electrical conductivity, as well as a range of shapes, sizes and pore size distributions are being constantly developed and tested as potential supercapacitor electrodes. In this thesis, the electrochemical behavior of a highly microporous activated carbon was studied as electrode for symmetric and asymmetric capacitors in acid and neutral media. The highest capacity and energy density values were obtained in the case of the activated carbon in acid solution.
Dottorato di ricerca in Science and Engineering of Environment, construction and Energy. Ciclo XXXII
Keywords: Plasmon; EELS; 2D materials; Carbon materials; Supercapacitor